The Role of Deagriarisation Process in Creating Threats for the Regional Economy and Nature in Selected Conservation Areas in South-Eastern Poland - Kamila MUSIAL; Wieslaw MUSIAL (Communications of International Proceedings, 2020)
Nowadays a loss of biodiversity in Poland may result not only from excessive intensification of agriculture, but in some regions also from the opposite process of abandonment of agricultural use. The study was conducted in 2019-2020, in 30 communes/municipalities, within 3 conservation areas, where traditionally some agricultural activities are still present. In order to show the level of deagrarisation and deanimalisation processes, there was used the zero unitarisation method that indicate an abandonment of agricultural production, mainly for economic reasons. Moreover, there were carried out some botanical research in seminatural plant communities, to show if there is the connection between advancement of deagrarisation, and deanimalisation process and the total number of vascular plant species and distribution of rare species. The results show that there are mutual connections between diversity of plant species, structure of the landscape and its management. In those communes where the deagrarisation process was highly advanced, there was small number of plants in phytosocological releves. The lowest percentage of abandoned farming was noted in the municipalities with relatively good soils, that are located in the Nadnidzianski Landscape Park. That was also the area with the highest number of plants in releves (on average 45-53). Deagrarisation and deanimalisation processes were particularly intensified in the communes located in the northern part of Konecko-Lopusznianski Nature Park, where deagrarisation advancement was > 0.372.
Keywords: Deagriarisation and Deanimalisation; Natural Capital; Mutual Connections.